Methane recovery from anaerobic digestion of urea-pretreated wheat straw. (January 2018) - Yao, Yiqing; Bergeron, Andre David; Davaritouchaee, Maryam
Abstract: Pretreatment is necessary to improve methane production from lignocellulosic biomass. Urea was adopted to pretreat wheat straw with the advantages of structure deconstruction, its nitrogen source, and prevention of pH drop in subsequent anaerobic digestion (AD). Scanning electron microscopy (SEM), X-ray diffraction analysis (XRD) and Fourier transform infrared spectroscopy (FTIR) spectra measurements indicated that urea pretreatment is able to degrade the lignocellulosic structure, which was beneficial for the improvement of methane production. Urea pretreatment led to the satisfactory performance of AD with wheat straw as substrate. The maximum methane production of 305.5 L/kg volatile solids (VS) was obtained using 1% (w/w) urea loading, which was 45.2% higher than the untreatment. After 1%- and 3%-urea treatment, time used for achieving stable status (≥50%) was 2 days earlier compared to untreatment. Reductions of total solids (49.4%), VS (54.5%), cellulose (50.4%) and hemicelluloses (47.3%) on the optimal condition were the highest, which were 36.8%, 46.5%, 33.3% and 47.4% higher compared to untreatment. Higher levels of urea pretreatment (3% and 5%) were less efficient and resulted in the formation of pseudo-lignin according to FTIR. These results indicate that wheat straw can be used to produce methane significantly with urea pretreatment. Highlights: Lignocellulosic structure was degraded by urea pretreatment. Urea pretreatment had positive effect on methane production from wheat straw alone. The highest methane production was obtained at 1.0%-urea with 25:1 of C/N ratio. Formation of pseudo-lignin was occurred at high urea loading.